PENDAMPINGAN AKHLAK KARIMAH SANTRI MELALUI PEMBELAJARAN KITAB KUNING TAISIRUL KHALAQ PONDOK PESANTREN MIFTAHUL ISTIQOMAH SUNGAI GERINGGING PADANG PARIAMAN - Abdul Farid; Martin Kustati; Rezki Amelia (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Abstract. The aim of this assistance is to form the Akhlakul Karimah of students at the Miftahul Istiqomah Islamic boarding school through learning the yellow book about taisirul khalaq. Akhlakul Karimah assistance through studying the yellow book Taisirul Khalaq is an assistance carried out to provide an understanding of morals to students. This is done because the degradation of manners and morals experienced by the young generation of Muslims is currently increasingly worrying. Islamic boarding schools play a very important role in developing morals for students. Even though Islamic boarding schools have done their best in developing the morals of their students, there are still many students whose morals are not good, which is why this assistance is provided. Mentoring is carried out using the halaqah method, a method often used in Islamic boarding schools, namely students will learn by sitting around the teacher and listening together to what the teacher is saying. The results of this mentoring help students who are not yet very familiar with the parts of morals to become aware of morals and be able to practice them in their daily lives. From this assistance, they are also more enthusiastic about living their lives because they are taught to always be grateful and accept their fate or circumstances. Even though there are several obstacles in this assistance, such as limited time, the students remain enthusiastic so they can maximize their time efficiently.